Four dead in Ohio : the global legacy of youth activism and state repression - Solomon, Johanna (Emerald Publishing Limited, 2021)
This Special Issue of Research in Social Movements, Conflicts and Change reflects upon global student and youth activism 50 years after the infamous May 4, 1970 National Guard shootings of student activists demonstrating against the US wars in Vietnam and Cambodia at Kent State University in Ohio, USA. That incident drew attention to state violence and youth attempts to build peace. However, it was neither the first nor last time student movements faced violent opposition during protests for peace, equity, democracy, and structural change. This volume examines how youths mobilized for change, faced repression, and were commemorated. The first section focuses on how society views and responds to youth and student political engagement. Chapters assess mobilizing a global movements; how fear of and constraints on youth undermine activism, and the construction student peace programming. The second section highlights how violent repression of students and youth occurs around the world, with chapters addressing how student movements evolve in response to violence. The final section of this volume examines the contestation and commemoration of activism and violence. Taken together, this volume provides much needed space for the narratives of those youths and students who have fought, and continue to fight, for change.
Includes index.
Keywords: Youth -- Political activity.; Political violence.; Youth movements.; Kent State Shootings, Kent, Ohio, 1970.; Political Science -- Political Ideologies / Radicalism.; Political activism.; elektronické knihy; electronic books